LEXICOGRAPHIC REPRESENTATION OF HUMOROUS POLYSEMY - Kendjaeva Zemfira (Modern American Journals, 2025)
Many bilingual and learner’s dictionaries leave the humorous potential of polysemous words undocumented, masking pragmatic contrasts that are vital in cross‑cultural communication. Building on recent research into usage‑label design and on theoretical models of verbal humour, this article reviews the treatment of humorous polysemy in major English dictionaries, identifies the gaps that arise when “hum.” or “facetious” labels are omitted or inconsistently applied, and proposes a principled framework for signalling comic meanings. The framework combines micro‑labels (hum., joc., facet.) with sense‑division strategies and corpus‑based attestation rules, offering lexicographers concrete guidelines for marking humour so that users can decode and encode nuance with greater accuracy.
Keywords: Lexicography; humour; polysemy; usage labels; bilingual dictionaries; sense disambiguation; corpus evidence; pragmatics